2020
DOI: 10.3390/diagnostics10110861
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Analysis of Pyogenic Vertebral Osteomyelitis Immediately after Successful Antimicrobial Therapy: Considerations for Assessing Therapeutic Response

Abstract: Purpose: The clinical and radiological abnormal findings continue even after successful treatment in pyogenic vertebral osteomyelitis (PVO). We analyzed the clinical and radiological features of cured PVO based on 18F-fluorodeoxyglucose positron emission tomography/magnetic resonance imaging (FDG-PET/MRI) and compared the radiological differences between FDG-PET and MRI for assessing therapeutic response in PVO. Methods: This study included 43 patients (28 men and 15 women) with lumbar PVO who had no recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In accordance with other studies, the majority of our PVO population was found to consist of elderly men presenting with back pain and elevated CRP (Chang et al, 2018;Chong et al, 2018;Jeon et al, 2020;Kim et al, 2020;Vettivel et al, 2019). These findings were consistent with a previous study from our institution by Aagaard et al, using a similar design, on 100 PVO patients admitted from 2006 to 2011 (Aagaard et al, 2013).…”
Section: Comparison With the Literaturesupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with other studies, the majority of our PVO population was found to consist of elderly men presenting with back pain and elevated CRP (Chang et al, 2018;Chong et al, 2018;Jeon et al, 2020;Kim et al, 2020;Vettivel et al, 2019). These findings were consistent with a previous study from our institution by Aagaard et al, using a similar design, on 100 PVO patients admitted from 2006 to 2011 (Aagaard et al, 2013).…”
Section: Comparison With the Literaturesupporting
confidence: 93%
“…In general, our study reported similar demographics and comorbidities to those in previous reports (Chong et al, 2018;Jeon et al, 2020;Kim et al, 2020;Lee et al, 2019).…”
Section: Comparison With the Literaturesupporting
confidence: 87%
“…Jeon et al [ 14 , 15 ] investigated the change of FDG uptake according to the phases of osteomyelitis based on the pathophysiological features of osteomyelitis. The early phase of PVO is characterized by activated neutrophil accumulation, known as the respiratory burst, which uses greater amounts of glucose as the main energy source for chemotaxis and phagocytosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they emphasized the increase of diagnostic accuracy for detecting residual PVO using 18 F-FDG-PET and CRP together. In addition, the clinical and radiological characteristics according to anatomical location of major structural damage were analyzed in patients with cured PVO, which was expected to be very helpful for determining therapeutic response in clinical field [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated erythrocyte segmentation rate (ESR, normal range: < 25 mm/h) or C-reactive protein (CRP, normal range: < 0.5 mg/dL) level or both along with speci c magnetic resonance (MR) ndings of PVO as a contiguous single lesion was an important clue for the diagnosis of PVO. In the extent of PVO lesion, a PVO lesion comprises the upper and lower vertebrae centering on the infected disc with or without epidural, psoas, and paraspinal abscesses; it was de ned as one level (e.g., if there were two infected discs, then three vertebrae were included centering on the two infected discs, this PVO lesion was considered two levels) [9] .…”
Section: Diagnosis Of Pvomentioning
confidence: 99%